2005
DOI: 10.1038/sj.jcbfm.9600083
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of Neuronal Activity in Rat Whisker-Barrel Cortex Sensory Pathway from Freezing Injury after Transplantation of Adult Bone Marrow Stromal Cells

Abstract: The effect of transplantation of adult bone marrow stromal cells (MSCs) into the freeze-lesioned left barrel field cortex in the rat was investigated by measurement of local cerebral glucose utilization (lCMR(glc)) in the anatomic structures of the whisker-to-barrel cortex sensory pathway. Bone marrow stromal cells or phosphate-buffered saline (PBS) were injected intracerebrally into the boundary zone 1 h after induction of the freezing cortical lesion. Three weeks after surgery, the 2-[(14)C]deoxyglucose meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Only a few studies have been run to elucidate the effect of BMSC transplantation on brain function. Using an autoradiography technique, Mori et al found that BMSC transplantation significantly improved glucose metabolism in the thalamus and barrel cortex in response to whisker stimulation after neocortical freezing injury (19). We also showed that BMSC transplantation significantly improved the binding potential of 125 Iiomazenil, a radioactive ligand selective for the central type of benzodiazepine receptor, in the periinfarct area.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Only a few studies have been run to elucidate the effect of BMSC transplantation on brain function. Using an autoradiography technique, Mori et al found that BMSC transplantation significantly improved glucose metabolism in the thalamus and barrel cortex in response to whisker stimulation after neocortical freezing injury (19). We also showed that BMSC transplantation significantly improved the binding potential of 125 Iiomazenil, a radioactive ligand selective for the central type of benzodiazepine receptor, in the periinfarct area.…”
Section: Discussionmentioning
confidence: 64%
“…Other recent studies have suggested that MRI and optical imaging might provide useful information on the engraftment of BMSCs in the host CNS (14)(15)(16)(17)(18). However, there are few studies that indicate the utility of an imaging technique to monitor the response of the host CNS after cell therapy (19)(20)(21).…”
mentioning
confidence: 99%
“…It is believed that this test is superior to the Rogers test because the score is assigned in a more objective manner. In similar studies, functional improvement in rotarod test has been demonstrated when bone marrow derived MSC (MSC-bm) [40][41][42][43] or adipose tissue-derived MSC (MSC-a) [23] were used.…”
Section: Adipose Tissue-derived Msc Administration Improved Functionamentioning
confidence: 88%
“…After neurotransplantation MSC react to the brain microenvironment signals and differentiate into glia and neurons [1,13]. Moreover, numerous studies showed that after intravenous or intracerebral transplantation MSC promote restoration and regeneration of the nervous tissue in injuries to the brain and spinal cord, though the mechanisms of their effect are virtually unknown [3,12,13,25].…”
mentioning
confidence: 99%